Effect of toasted Adenanthera paavonina seed meal on haematology and blood chemistry of finisher broilers - Ukpabi, Ugochukwu Hart (Journal of Agricultural Sciences (Belgrade), 2018)
The effect of graded levels of toasted Adenanthera pavonina seed meal (TAPSM) on haematological and biochemical indices of finisher broilers was investigated in a five-week feeding trial with 84 5-week old broilers divided into four groups of 21 birds per group. Each group had three replicates of 7 birds. Four experimental diets were formulated to contain 0, 10, 20 and 30% TAPSM, represented as T1, T2, T3 and T4 respectively. Birds were allocated to the four diets in a completely randomized design and housed in a deep litter pen. Feed and water were offered to birds ad libitum. Haematological parameters showed a significant (P